Sanksi Hukum Bagi Petugas Lembaga Pemasyarakatan yang Terlibat Peredaran Narkotika di Lingkungan Lembaga Permasyarakatan - I Kadek Pasek Saputra; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Interpretasi Hukum, 2021)
As a developing country with the state ideology Pancasila, it is not enough for the State of Indonesia to be able to dedicate itself as a prosperous country. Viewed from a legal perspective, there are behaviors that are in accordance with the prevailing norms and there are also behaviors that deviate from the prevailing norms. Nevertheless, it is necessary to have legal sanctions regulating the life of the nation and state. In the criminal justice system in Indonesia, the correctional institution has a position as a place of guidance and implementation of what has been decided by the court for the convicted person. There are two problem formulations that will be discussed further related to the criminal act of looting, including how the classification of abuse of power carried out by prison officers against the circulation of narcotics that occurs in prisons and how to impose legal sanctions for prison officers who are involved in narcotics trafficking in prisons? From the formulation of the problem, the discussion is carried out using normative research methods. The abuse of authority of correctional officers is regulated in Law no. 12 of 1995 concerning Correctional Facilities.